An integration-biased BER-aware design methodology of a BPSK transceiver front-end for power line sensor nodes - Ortiz, Joana Rochelle R. (College of Engineering, University of the Philippines Diliman, 2014)
To adapt to the low harvested energy available in sensor nodes, communication modulators and demodulators are now being implemented in the digital domain. To achieve a BER of 10e-6, the sole requirement of the Smartwire digital BPSK demodulator from its analog front-end counterpart is to maintain a maximum zero-crossing variation of 15 percent at all corners of the 65nm CMOS process, across the power line temperature variation of 0A ̂ to 100A ̂°C. In this thesis, the metrics critical to the zero-crossings were analyzed, and were identified as the input signal Signal-to-Interference-and-Noise Ratio (SINR), the total transceiver chain gain, the receiver's common mode voltage, and the comparator's trip points. Furthermore, the system level and circuit level non-idealities contributing to errors in these metrics were determined; and an integration-biased system level to circuit level design methodology of the analog transceiver front-end, which reduces these error sources, is presented. Complying with the system gain ang phase error distribution, a Class D Switching Power Amplifier with a narrowband filter was implemented as the transmitter, having an output power of up to -0.81dBm, maximum phase distortion of 0.1 percent, at an RMS power consumption of 2.04mW. To achieve impedance matching while providing the target gain, a fully differential two-stage gm-amplifier, in a shunt feedback configuration, was implemented as the LNA. Inherent resistive common-mode feedback was used to minimize common mode variation and increase PSRR. Optimal trip points for analog-to-digital conversion in the receiver back-end were derived as well. Integrating the whole transceiver chain, together with its LDO power supply, provided a maximum of only 13.04 percent zero-crossing distortion to the demodulator input, while consuming an average power of only 434uW.